2023
DOI: 10.1371/journal.pone.0282429
|View full text |Cite
|
Sign up to set email alerts
|

Origin identification of Cornus officinalis based on PCA-SVM combined model

Abstract: Infrared spectroscopy can quickly and non-destructively extract analytical information from samples. It can be applied to the authenticity identification of various Chinese herbal medicines, the prediction of the mixing amount of defective products, and the analysis of the origin. In this paper, the spectral information of Cornus officinalis from 11 origins was used as the research object, and the origin identification model of Cornus officinalis based on mid-infrared spectroscopy was established. First, princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Accordingly, Principal Component Analysis (PCA) [ 49 ] has been performed on the input features of train and test sets to reduce the noise and correlation from the data to improve the performance of the model. It has reduced feature space dimensionality to improve the accuracy of classification models.…”
Section: Data Preparationmentioning
confidence: 99%
“…Accordingly, Principal Component Analysis (PCA) [ 49 ] has been performed on the input features of train and test sets to reduce the noise and correlation from the data to improve the performance of the model. It has reduced feature space dimensionality to improve the accuracy of classification models.…”
Section: Data Preparationmentioning
confidence: 99%
“…26 Jin et al used PCA to dimensionalize the Cornus officinalis spectral data, and then realized the identication of Cornus officinalis origin using SVM, and the results indicated that the accuracy of this combined model was 84.8%. 27 Cornus officinalis is the dried mature fruit pulp of Cornus officinalis, a plant in the Cornaceae family. 28 It has the effects of tonifying the liver and kidneys, astringent and astringent, in addition to its cardiotonic, anti-inammatory, antibacterial, anti-stress, antioxidant and hypolipidemic effects.…”
Section: Introductionmentioning
confidence: 99%
“…26 Jin et al used PCA to dimensionalize the Cornus officinalis spectral data, and then realized the identification of Cornus officinalis origin using SVM, and the results indicated that the accuracy of this combined model was 84.8%. 27…”
Section: Introductionmentioning
confidence: 99%